Peripheral nerve block anesthesia/analgesia for patients undergoing primary hip and knee arthroplasty: recommendations from the International Consensus on Anesthesia-Related Outcomes after Surgery (ICAROS) group based on a systematic review and meta-analysis of current literature. Issue 11 (25th August 2021) - Memtsoudis, Stavros G; Cozowicz, Crispiana; Bekeris, Janis; Bekere, Dace; Liu, Jiabin; Soffin, Ellen M; Mariano, Edward R; Johnson, Rebecca L; Go, George; Hargett, Mary J; Lee, Bradley H; Wendel, Pamela; et al.
Abstract : Background: Evidence-based international expert consensus regarding the impact of peripheral nerve block (PNB) use in total hip/knee arthroplasty surgery. Methods: A systematic review and meta-analysis: randomized controlled and observational studies investigating the impact of PNB utilization on major complications, including mortality, cardiac, pulmonary, gastrointestinal, renal, thromboembolic, neurologic, infectious, and bleeding complications. Medline, PubMed, Embase, and Cochrane Library including Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, NHS Economic Evaluation Database, were queried from 1946 to August 4, 2020. The Grading of Recommendations Assessment, Development, and Evaluation approach was used to assess evidence quality and for the development of recommendations. Results: Analysis of 122 studies revealed that PNB use (compared with no use) was associated with lower ORs for (OR with 95% CIs) for numerous complications (total hip and knee arthroplasties (THA/TKA), respectively): cognitive dysfunction (OR 0.30, 95% CI 0.17 to 0.53/OR 0.52, 95% CI 0.34 to 0.80), respiratory failure (OR 0.36, 95% CI 0.17 to 0.74/OR 0.37, 95% CI 0.18 to 0.75), cardiac complications (OR 0.84, 95% CI 0.76 to 0.93/OR 0.83, 95% CI 0.79 to 0.86), surgical site infections (OR 0.55 95% CI 0.47 to 0.64/OR 0.86 95% CI 0.80 to 0.91), thromboembolism (OR 0.74, 95% CI 0.58 to 0.96/OR 0.90, 95% CI 0.84 to 0.96) and blood transfusion (OR 0.84, 95% CI 0.83 to 0.86/OR 0.91, 95% CI 0.90 to 0.92). Conclusions: Based on the current body of evidence, the consensus group recommends PNB use in THA/TKA for improved outcomes. Recommendation: PNB use is recommended for patients undergoing THA and TKA except when contraindications preclude their use. Furthermore, the alignment of provider skills and practice location resources needs to be ensured. Evidence level: moderate; recommendation: strong.